The economic burden of chronic diseases: Estimates and projections for China, Japan, and South Korea - Bloom, D.; Chen, S.; Kuhn, M.; McGovern, M.; Oxley, Leslie; Prettner, K. (2019)
We propose a novel framework to analyze the macroeconomic impact of non-communicable diseases. We incorporate measures of disease prevalence into a human capital augmented production function, which enables us to determine the economic burden of chronic health conditions in terms of foregone gross domestic product (GDP). Unlike earlier frameworks, this approach allows us to account for i) variations in human capital for workers in different age groups, ii) mortality and morbidity effects of non-communicable diseases, and iii) the treatment costs of diseases. We apply our methodology to China, Japan, and South Korea, and estimate the economic burden of chronic conditions in five domains (cardiovascular diseases, cancer, chronic respiratory diseases, diabetes, and mental health conditions). Overall, total losses associated with these diseases over the period 2010–2030 are (measured in real USD with the base year 2010) estimated to be $7.7 trillion for China, $3.5 trillion for Japan, and $1 trillion for South Korea.